Recent Positive Selection Drives the Expansion of a Schizophrenia-associated Variant within 10q24.33 in Human Populations through Its Pleiotropic Effects on Diverse Human Complex Traits. Issue 1 (2017) - Li, Lingyi; , Ming Li; Chang, Hong; Huang, Tao; Zheng, Yan; Qi, Lu; Xiao, Xiao
No abstract available